Occupational exposure to sevoflurane following topical application to painful wounds - Fernández-Ginés, Dámaso; Selva-Sevilla, Carmen; Cortiñas-Sáenz, Manuel; Gerónimo-Pardo, Manuel (La Medicina del Lavoro, 2019)
Background: Occupational exposure to halogenated anesthetics employed for general anesthesia has been extensively studied. Conversely, a new modality of treatment of painful wounds with topical sevoflurane lacks exposure studies. Objectives: To evaluate the magnitude of acute occupational exposure to sevoflurane following topical application to painful wounds. Methods: Four patients with chronic painful wounds were treated with topical sevoflurane (20, 20, 20 and 10 mL) following an approved therapeutic protocol in our Pain Management Unit. Eight passive dosimeters were placed at different locations of a treatment room with a volume of 163 m3 and 3.3 air changes per hour: 3 for near peak (for 20-50 min) and 1 overall exposure (for 3.4 h) at the nurse’s breathing zone, and 4 for area exposure (for 3-3.4 h). Worst-case scenario theoretical concentrations of sevoflurane were also calculated. Results: The highest levels were obtained for two dosimeters worn by the nurse at the breathing zone (8.28 and 9.12 ppm-TWA [parts per million-Time-Weighted Average]), while the lowest level was obtained from the dosimeter placed on the most distant wall from patients (0.73 ppm-TWA). Theoretical concentrations were calculated from standard volatilization principles and were in agreement with the concentrations measured. Discussion-Conclusions: All air concentrations measured were lower than exposure limits set by occupational safety agencies from Finland, Sweden and Norway, which range from 10 ppm for a TWA of 8 hours to 20 ppm for short-term exposures (15 min). Application of topical sevoflurane on wounds seems to be environmentally safe for health-care professionals as it produces exposure levels lower than the established limits for anesthetic procedures.